2011
DOI: 10.1111/j.1365-2672.2010.04931.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of bacteriophage endolysin EL188 and outer membrane permeabilizers against Pseudomonas aeruginosa

Abstract: Aims:  To select and evaluate an appropriate outer membrane (OM) permeabilizer to use in combination with the highly muralytic bacteriophage endolysin EL188 to inactivate (multi‐resistant) Pseudomonas aeruginosa. Methods and Results:  We tested the combination of endolysin EL188 and several OM permeabilizing compounds on three selected Ps. aeruginosa strains with varying antibiotic resistance. We analysed OM permeabilization using the hydrophobic probe N‐phenylnaphtylamine and a recombinant fusion protein of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 28 publications
3
96
0
Order By: Relevance
“…Permeabilizers can also enable the use of new antimicrobial compounds that are not very effective because of their low ability to enter the cell. For instance, bacteriophage endolysin EL188, which was considered to be limited to Gram-positive pathogens, inhibited P. aeruginosa when combined with certain outer membrane permeabilizers, in particular EDTA (25).…”
Section: Outer Membrane Permeabilizersmentioning
confidence: 99%
“…Permeabilizers can also enable the use of new antimicrobial compounds that are not very effective because of their low ability to enter the cell. For instance, bacteriophage endolysin EL188, which was considered to be limited to Gram-positive pathogens, inhibited P. aeruginosa when combined with certain outer membrane permeabilizers, in particular EDTA (25).…”
Section: Outer Membrane Permeabilizersmentioning
confidence: 99%
“…EDTA), or high hydrostatic pressure in combination with an endolysin have been studied. 21,22,91,92 Although these measures have shown that chemical and/or physical disruption of the outer membrane allows the endolysin to gain access to the protected peptidoglycan, they may not lend themselves well to human therapies. These methods have not always been successful, with some Gram-negative strains remaining insensitive to lysis by endolysins after membrane disruption.…”
Section: Gram-negative Bacteria Infectionsmentioning
confidence: 99%
“…Thus, antibacterial activity has only been shown to be possible after treatment of the outer membrane of Gram-negative cells with EDTA [116] or by the fusion of hydrophobic amino acids to the endolysin, which enables the movement of the endolysin across the outer membrane. The latter approach has been recently developed in endolysins by the group of Lavigne in Belgium [117] and was based on earlier observations where the action of lysozyme against E. coli was enhanced by the fusion of a hydrophobic pentapeptide onto the C-terminus [118]. The advantage of the use of lysins over other antibacterials (or antibiotics) is their specificity for one bacterial pathogen without disturbing other nonpathogenic bacterial flora.…”
Section: Phage Endolysins As Therapeuticsmentioning
confidence: 99%